Musculoskeletal symptoms in support staff in a large telecommunication company. - Fagarasanu M; Kumar S (Work, 2006)
PRIMARY OBJECTIVE: The primary objective of this study was to determine the extent and severity of the musculoskeletal problems in office workers in a telecommunication company. RESEARCH DESIGN: A questionnaire survey was conducted to assess the prevalence of musculoskeletal disorders' symptoms, their perceived intensity and interaction with ability to work among office workers. METHODS AND PROCEDURES: The Cornell Musculoskeletal Discomfort Questionnaire and Cornell Hand Discomfort Questionnaire developed by the Human Factors and Ergonomics Laboratory at Cornell University were used on a sample of 140 office workers in a telecommunication company. MAIN OUTCOMES AND RESULTS: Discomfort/pain/ache at the wrist level was reported by 86.5% for the left side and 95.5% for the right side. Additionally, discomfort/pain/ache was reported by 77.5% of the sample for neck and 31% of the sample for the left and 50% for the right shoulder region. At the hand site, the area in the distal proximity of the wrist was the most affected site being indicated in 90% of cases for left side and 95% of cases for the right side. CONCLUSIONS: An overview of problems associated with the body parts in office work may allow targeted prevention and intervention.